Comparison of Alexithymia in Athlete and Non-Athlete Students - Heidar Jodat; Abdollah Ghasempour; Abotaleb Tavakoli (The Society of Aging and Physical Activity (SAPA), 2015)
Today, researchers consider sports as one of the methods of reinforcement in the development of psychological parameters. The aim of the present study was to compare the alexithymia and its components, in athletes and non-athletic adolescents. Its components consist of difficulty in identifying feelings (DIF), difficulty in describing feelings (DDF), and externally oriented thinking (EOT). The statistical sample of the research included 100 athlete students and 100 non-athlete students, who were selected using multistage cluster sampling. They were asked to fill out the Farsi version of the Toronto Alexithymia Scale-20. The obtained results showed that there were significant differences in the mean scores of the alexithymia and its three components: difficulty in identifying feelings, difficulty in describing and externally oriented thinking in both groups (P = 0.001, P = 0.001, P = 0.001 and P = 0.008, respectively). The results revealed that athletic students had less emotional problems than non-athlete students; it is recommended that physical activity be part of the strategies to improve emotional health among non-athletic students.